2006
DOI: 10.1021/np060339k
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Transformation of Amino- and Hydroxyanthraquinones by Beauveria bassiana ATCC 7159

Abstract: Microbial biotransformation of four amino- and hydroxyanthraquinones catalyzed by Beauveria bassiana ATCC 7159 has been studied. Incubation of 1,2-diaminoanthraquinone (1) with B. bassiana ATCC 7159 afforded 1-amino-2-(4'-O-methyl-2beta-N-D-glucopyranosylamino)anthraquinone (5) in a hitherto unprecedented biotransformation involving N-glycosylation of an amine. Biotransformation of 1-aminoanthraquinone (2) yielded 1-amino-2-(4'-O-methyl-2beta-O-D-glucopyranosyloxy)anthraquinone (6) as a result of microbial hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 15 publications
(11 reference statements)
1
18
0
Order By: Relevance
“…B. bassiana and Cunninghamella spp. have been used for glycosylation of other phenolic natural products (Ibrahim et al 1997;Zhan & Gunatilaka 2006). Our results showed that B. bassiana and C. echinulata var.…”
Section: Resultsmentioning
confidence: 70%
“…B. bassiana and Cunninghamella spp. have been used for glycosylation of other phenolic natural products (Ibrahim et al 1997;Zhan & Gunatilaka 2006). Our results showed that B. bassiana and C. echinulata var.…”
Section: Resultsmentioning
confidence: 70%
“…These proton signals were easily linked to the new carbon signals at d 98. 4 38,39) and shown in Table 2. Further evidence came from the 3 3.44 3H, s CH 3 1.02 (d, 6) sylation was deduced from the H-1Љ/C-7 correlation observed in the HMBC spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…A wide variety of anthraquinone derivatives isolated from plants, animals and marine fungi have served as candidates for various therapeutic uses [13]. Anthraquinones inhibit the proliferation of human breast, colon and lung cancer cells [4].…”
Section: Introductionmentioning
confidence: 99%